Relationship between Moral Development by TPA Teachers and Children's Social Behavior in TPA / TPQ Mesjid Al-Iman, Gunung Sarik Village, Kuranji District, Padang City - Septiani Dwi Cahya; Wirdatul Aini (Universitas Negeri Padang, 2021)
This research was motivated by the lack of social behavior of children at the TPA of the Al-Iman Mosque, this is presumably due to the low moral development given by teachers to children. This study aims to: 1) describe moral development by TPA teachers; 2) describe the child's social behavior; and 3) looking at the relationship between moral development by TPA teachers and children's social behavior in TPA Mesjid Al-Iman, Gunung Sarik Village, Kuranji District, Padang City. The approach in this research is a quantitative approach with correlational research type. The population in this study were all children who participated in the TPA at Al-Iman Mosque, amounting to 54 children, while the sample taken was 34 people using the stratified random sampling method. Data collection techniques in this study used structured interviews with data collection tools in the form of a list of statements. The data analysis technique used the percentage formula and product moment correlation. The results showed that; 1) moral development by TPA teachers at TPA Mesjid Al-Iman is still categorized as low, 2) social behavior of children at TPA Al-Iman is categorized as poor, and 3) there is a significant relationship between moral development by TPA teachers and children's social behavior in TPA Al-Iman Mosque, Gunung Sarik Village, Kuranji District, Padang City.Keywords: Moral Development, Social Behavior, Al-Qur'an Education Park